Manidipine: an antihypertensive drug with positive effects on metabolic parameters and adrenergic tone in patients with diabetes - Margarita SaizSatjes; Francisco Javier Martinez-Martin (BioExcel Publishing Ltd, 2018)
Antihypertensive treatment of patients with diabetes should include those drugs with a positive effect on metabolic parameters. Most patients with diabetes require at least two antihypertensive agents. Combining a dihydropyridine calcium channel blocker with a renin-angiotensin-aldosterone system inhibitor is a rational approach. However, not all dihydropyridines are equal with respect to their effects on metabolic parameters. Thus, manidipine exerts a positive effect on insulin resistance. However, this effect has not been observed with amlodipine. On the other hand, the excessive activation of sympathetic nervous system has been related with an increase of insulin resistance, pulse pressure, and ankle edema rates. Compared with amlodipine, manidipine activates sympathetic nervous system to a lesser extent. As a result, treatment with manidipine represents a good option in hypertensive patients with diabetes.